BALA PALA INDONESIA: CREATIVE PROCESS OF CONCEPTUAL ILLUSTRATION BASED ART FASHION - Mudarahayu, Tiartini (Bajang Institute, 2025)
Banda nutmeg sparked conflict, until thenegotiations culminated in the signing of three peace treaties known as the Treaty of Breda, one of which concerned the exchange of Run Island and Manhattan. Seeing Banda nutmegas a subject that can be read as a source of inspiration with an interdisciplinary basis for art fashion, the author chose illustrations with the phenomenon of `Cinderella` art as the background, as a medium for expressing the work. The method used is the elaboration of frangipani and three aesthetic approaches by referring to the theoretical foundations of creativity, product semantics, and phenomenological aesthetics. The results of the research synthesis of creation in the form of novelty conceptual illustration works based on art fashion in the collection of works